Plasma in situ gas–liquid nitrogen fixation using concentrated high-intensity electric field. (18th September 2019) - Peng, Peng; Schiappacasse, Charles; Zhou, Nan; Addy, Min; Cheng, Yanling; Zhang, Yaning; Anderson, Erik; Chen, Dongjie; Wang, Yunpu; Liu, Yuhuan; Chen, Paul; Ruan, Roger
Abstract: The environmental issues associated with the Haber–Bosch industry urges research on alternative nitrogen fixation processes. The efficiency of the plasma-based nitrogen fixation process could be greatly enhanced by eliminating hydrogen from the reactant stream and directly fixing nitrogen into the water-based solution. In this study, we present a novel non-thermal plasma gas–liquid nitrogen fixation process that generates plasma in situ within the liquid body using concentrated high-intensity electric field (CHIEF). The CHIEF system also avoided discharge at the electrode, which could help reduce electrode corrosion. The effects of input power and conductivity on discharge performance and nitrogen product composition were analyzed. The CHIEF system achieved a fixation rate as high as 11.2 µ mol min −1 . This system improved the selectivity towards nitrate compared with plasma generation at the water surface.